2015
DOI: 10.1051/parasite/2015024
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorhabdosynochusspecies (Monogenoidea, Diplectanidae) parasitizing groupers (Serranidae, Epinephelinae, Epinephelini) in the western Atlantic Ocean and adjacent waters, with descriptions of 13 new species

Abstract: Seventeen of twenty-three species of groupers collected from the western Atlantic Ocean and adjacent waters were infected with 19 identified species (13 new) of Pseudorhabdosynochus Yamaguti, 1958 (Dactylogyridea, Diplectanidae); specimens of the Spanish flag Gonioplectrus hispanus, coney Cephalopholis fulva, marbled grouper Dermatolepis inermis, mutton hamlet Alphestes afer, and misty grouper Hyporthodus mystacinus were not infected; the yellowmouth grouper Mycteroperca interstitialis and yellowfin grouper My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 34 publications
(27 reference statements)
2
27
0
4
Order By: Relevance
“…Kritsky, Bakenhaster & Adams (2015) compared specimens from both sides of the Atlantic, did not find any morphological features that distinguished specimens from these localities, and concluded, as did Santos, Buchmann & Gibson (2000), that the specimens were conspecific. In contrast to our findings for P. sulamericanus , in that case the hosts were also conspecific ( M. marginata) .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Kritsky, Bakenhaster & Adams (2015) compared specimens from both sides of the Atlantic, did not find any morphological features that distinguished specimens from these localities, and concluded, as did Santos, Buchmann & Gibson (2000), that the specimens were conspecific. In contrast to our findings for P. sulamericanus , in that case the hosts were also conspecific ( M. marginata) .…”
Section: Discussionmentioning
confidence: 92%
“…However, in specimens from H. niveatus , the primary canal—primary chamber continuity could be seen, but we evaluated far fewer of these specimens and so cannot be sure about the range of morphological variability in this structure. The additional sclerotised material is visible in the drawings of the original description and probably mentioned as “enclosed in muscular, funnel-shaped organ” (Santos, Buchmann & Gibson, 2000); it is mentioned in its redescription as “surrounded by variable small sclerites” (Kritsky, Bakenhaster & Adams, 2015); none of these authors used a DIC microscope which provides a better resolution of the hollow sclerotised organs.
10.7717/peerj.2233/fig-5Figure 5 Pseudorhabdosynochus sulamericanus from Hyporthodus haifensis , haptor hard parts and squamodisc.(A, D) ventral bar, with method of measurement of length; (B) ventral anchor; (C) dorsal anchor; (E) lateral (dorsal) bar; (F) ventral squamodisc.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other localities: Off Rosas, Mediterranean Sea, France [ 25 ]; off Banyuls-sur-Mer, France [ 8 , 9 ]; off Ilhas Cagarras, Rio de Janeiro, Brazil [ 11 ]; off Ubatuba, coast of São Paulo, south-eastern Brazil [ 26 ]; off Barra Velha, State of Santa Catarina, Brazil [ 2 ]; Sfax (fish market), Tunisia (present study). The Bay of Naples, Italy is sometimes indicated as a locality based on Ulmer & James (1981) [ 27 ] but this paper does not describe the sclerotised vagina so it could be, in our opinion, any species of Pseudorhabdosynochus .…”
Section: Resultsmentioning
confidence: 99%
“…Pseudorhabdosynochus beverleyburtonae (Oliver, 1984) Kritsky & Beverley-Burton, 1986 is a gill parasite of the dusky grouper Mycteroperca marginata in the Mediterranean Sea and both sides of the Atlantic [ 2 , 8 – 11 ]. We found that three species of Pseudorhabdosynochus from groupers assigned to Mycteroperca Gill in the Mediterranean Sea and Eastern Atlantic Ocean were morphologically very close to P .…”
Section: Introductionmentioning
confidence: 99%